Lambakan perumahan kuota bumiputera di Negeri Perak dan kaedah mengatasinya - Kamal, Kamarul Idzham (2016)
Development in the housing sector cannot escape from a variety of problems which often overlap and haunting whether buyers, developers or even the government, such as the the oversupply and less marketable of Bumi housing quota in the development of the housing sector. A study was undertaken to identify the problem and find a solution and present the appropriate measures. The study area chosen is the state of Perak. A total of 30 questionnaires were distributed to 30 companies that have been shortlisted developers. The research includes provisions identify in Perak Bumi quota, reviewing the most difficult housing property sold by type, price and location of the property and to identify steps that can be done to solve the less marketable of Bumi housing quota in the development of the housing sector. The data was collected through observation, interview and questionnaire. Results from the analysis of the study, it was found that the demand for Bumi lot is still at a minimum level, especially for residential properties located in urban areas and high value. Therefore, for the continuation of the policy and the implementation of the Bumi quota then all parties must think collectively on the importance and responsibilities of each in fulfilling social goals. The results of this study can serve as a basis and guide improvements to overcome the oversupply and less marketable of Bumi quota in the development of the housing sector.